Assessment of present procurement process of private owned rural piped water supply implemented by Department of Public Health Engineering (DPHE) based on key performance indicators (KPI) - Akhter, Firoza (BRAC University, 2018)
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.